Analysis of Work Readiness of Vocational High School Students to Support the Success of Sustainability Development Goals (SDG’s) - Nurhaini, Lies (Proceedings of International Conference on Science, Education, and Technology, 2024)
The Sustainable Development Goals (SDGs) set by the United Nations (UN) in 2015 have a target to achieve 17 global goals, including poverty alleviation, hunger, and climate change. Vocational education and training play an important role in achieving this SDGs by equipping students with the skills and knowledge needed to enter the workforce and contribute to sustainable development. The purpose of this study is to deeply understand the work readiness of vocational high schools. This study is used to analyze the work readiness of vocational high school students to support the success of sustainable development goals. The research method used is literature review. The work readiness of vocational school students is an important factor in supporting the achievement of the SDGs. The level of work readiness of vocational school students varies, but in general it is still not optimal. One of the impacts of work readiness is unemployment. Factors that affect the job readiness of vocational school students include educational curriculum, training and skill development, work experience, soft skills, competition and access to information about job opportunities. Improving the job readiness of vocational school students can be done through various strategies, including updating the educational curriculum, improving training and skill development, and providing opportunities for students to gain work experience.